Placenta and Intestinal Injury in Preterm Infants - Garg, Padma; Weitkamp, Jörn-Hendrik; McDonald, Anna G.; Cilvik, Sarah N.; Mir, Imran; Shenberger, Jeffrey S.; Olaloye, Oluwabunmi; Konnikova, Liza; Kallapur, Suhas G.; Garg, Parvesh M. (American Journal of Perinatology, 2024)
Necrotizing enterocolitis (NEC) is one of the most common gastrointestinal conditions affecting 6 to 10% of low-birth-weight infants and remains a leading cause of death. The risk factors associated with NEC are complex and multifactorial, including preterm birth and intrauterine exposure to inflammation and hypoxia. Chorioamnionitis has been associated with intestinal injury in animal and human clinical studies. This review presents current evidence about the clinical impact of the intrauterine environment on intestinal injury during pregnancy and postpregnancy. We present information from our own clinical and laboratory research in conjunction with information collected from an extensive search in the databases PubMed, EMBASE, and Scopus. Prospective multicenter studies, including accurate and precise clinical, maternal, and laboratory predictors (e.g., inflammatory biomarkers), will help identify the mechanisms associated with the placental pathology, the development of NEC, and the impact of in utero-triggered inflammation on the clinical outcomes. Filling the knowledge gap to link the inflammatory surge to postnatal life will aid in identifying at-risk infants for NEC in a timely manner and facilitate the development of novel immunomodulatory treatments or interventions to improve the outcomes of these vulnerable infants.Key Points
Keywords: placenta; chorioamnionitis; NEC; intestinal injury; preterm infant